KESEIMBANGAN ANTARA PENDAPATAN DENGAN BIAYA OPERASIONAL KAPAL PENYEBERANGAN LINTAS JANGKAR-KALIANGET - Ilham, Chairul Insani; Darwan, Wawan (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
The existence of Port Jangkar has a very important role in supporting economic activities and equitable development in Situbondo since water transport is one of the modes of transportation that connects the island of Java and Madura Island. This study uses a quantitative approach. The theory used is proposed by Supranto (1990). The results showed that the productivity of freight traffic crossings serving Jangkar-Kalianget experienced decrease in revenue both passenger and goods transport by an average of 16, 6 percent. Based on the results of forecasting, demand for transportation, Break Even Point (BEP) load factor of 21 percent was achieved in 2011. In 2012, the company suffered losses in terms of transportation operating income due to declining productivity of vessel transport. In 2012 cruise companies suffered losses due to large vessel operating expenses exceeded the income from the vessel (BOK> Revenue) with the operational costs of Rp297,763,505; and vessels revenue of Rp2,709,255,500. Thus, in 2012 it was needed to subsidize the sustainability of Ferry transportation, because the Ferry transport activities cross Jangkar-Kalianget- Sapudi Island still has the potential transport demand and still needed the surrounding community.